SISTEM INFORMASI ADMINISTRASI NASABAH DI KSPPS NUR INSANI SEMARANG - Asmara, Yudha; Khoiri, Nur; Wijayanto, Wijayanto (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2023)
ABSTRACT- KSPPS Nur Insani is a sharia cooperative that has been established since 2013, almost 10 years running but still uses the old way of doing administration, namely with paper collections and installment books. This cooperative does not yet have an information system, it only has manual data archives. This process triggers fraud or inaccuracy of data in the collection process from both cooperatives and customers. This is also a supporting factor because in the current era many Indonesians like to use cellphones or laptops to keep records compared to using books or paper, because the system can minimize data loss when compared to paper or books. From some of these problems, a solution was provided, namely by creating a Customer Administration Information System at KSPPS Nur Insani Semarang which has 5 stages, namely: Communication, Planning, Modeling, Construction, and Deployment. In making the system using system design which includes: Flowcharts, Context Diagrams, DFD, ERD, Table Relations, DIPO. and use software including: PHP, MySQL, XAMPP, PHP, HTML, and Bootstrap. The results showed that the respondents' validation assessment using the Guttman scale as many as 15 respondents obtained an average result of 94% which was included in the "Very Eligible" criteria used. Then the results of the expert validation assessment using the Likert scale obtained an average result of 88.3% which was included in the "Very Eligible" criteria was used. Keyword : Information System, Administration, Customer